Hatchability Problem Of Exsitv Conservation Of The Freshwater Crocodile Crocodylus Palustris(Lesson 1831) At Dulahazra Safari Park, Cox’s Bazar, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2015)
In this research hatchability problems of freshwater crocodile in Dulahazra Safari Park have been discussed. The findings focused on meteorological factors, lack of suitable habitat in semi-captive enclosures and some physiological factors which are mainly responsible for non-hatchability of freshwater crocodile in the park environment. The research emphasized on finding rationale that interrupts breeding failure of this crocodile in this park. The hatchability problem was identified with some influential factors which are main barriers to escalate and proliferate the reintroduce program in Bangladesh. The findings showed that the influential factors including high stock density in a small space, low water deepness and narrow sandy bank of the enclosure with lack of nesting materials, high temperature and heavy rainfall are mainly responsible for the failure of freshwater crocodile breeding potentiality.Asiat. Soc. Bangladesh, Sci. 41(2): 155-161, December 2015